Characterization of allelopathic algicide produced by solid-state fermentation of okara byproducts - Voo, Amanda Ying Hui (Nanyang Technological University, 2025)
Harmful algae bloom (HAB) has become an increasingly worrisome problem with impact spanning across crucial industries, such as: agriculture, water utilities, recreation, and tourism. Despite the disadvantages of prolonged and indiscriminate use of traditional copper algicides, formulations containing copper has remained as one of the most utilized algicides on the market, with copper sulphate and chelated copper taking a major market share. Continual discovery and development of novel algicides which are biodegradable, operate at a species-specific level, and has limited negative impacts on the targeted ecosystems is crucial to update the toolbox which water managers use to remove and inhibit algae growth under specific applications. Among biological methods, direct bacteria-to-microalgae contact, and bacterial extracellular metabolites are identified as potential algicidal agents that can fulfil the demand for green and sustainable algicides. Often, the algicidal metabolites are presented as extracellular metabolites which bacteria, fungi, protozoans, and plants secrete into their living environment, whether as a direct reaction to the presence of microalgal competitors or with microalgal inhibition as a secondary unintended consequence. In Chapter II, the cell-free fermentate produced from the aerobic fermentation of P. chlororaphis in LB media exhibited a higher algal inhibition rate than those produced under microaerobic conditions against the tested strains (Chlorella sp. ATCC 14854 and P. tricornutum UTEX LB642); this result presents a stark contrast against previous studies. Later, the serendipitous discovery of a bright orange coloration within the fermentate served as a base hypothesis for the identification of potential algae-inhibiting metabolites produced by P. chlororaphis. Among the well-known, orange-colored metabolites of P. chlororaphis, phenazine derivatives (phenazine-1-carboxylic acid, PCA and phenazine-1-carboxamide, PCN) were hypothesized to be the active algae inhibiting component. A potential link was established between phenazine derivatives and algal inhibition rate (%) against Chlorella sp. (ATCC 14854) and P. tricornutum (UTEX LB642) based on the positive correlation between the concentration of phenazine derivatives produced as detected by HPLC-DAD analysis, and the incubation time of P. chlororaphis under aerobic condition. Aerobic fermentation produced a maximum concentration of phenazine derivatives at 26.48 μg/mL on the 72H of aerobic fermentation which coincided with the maximum algal inhibition rate of 72.25% after 24H incubation with Chorella sp. and suggests a concentration-dependent mode of algal inhibition. These results provided a theoretical foundation upon which further algicide discovery work can be built on. Considering the drawbacks of using traditional copper algicides in live aquaculture and agriculture processes and coupled by key market drivers in the APAC region where consumers are demanding more sustainable production processes, it is imperative to discover novel methods to sustainably produce algicides using existing byproduct and sidestreams generated from Singapore’s agri-food ecosystem. Chapter III of this thesis explores okara, an agricultural byproduct generated from soymilk production as a substrate for solid-state fermentation. It was used as the sole nutrient source in a ‘proof-of-concept’ experiment to sustain the growth of rhizosphere bacterium, P. chlororaphis and to produce the suspected algicidal extracellular metabolites – phenazine derivatives and rhamnolipids congeners in a batchwise solid-state fermentation. Using targeted LC-MS Q-ToF metabolomic analysis, the batch fermentation experiments found conclusive presence of phenazine-1-carboxylic acid (PCA) and potential presence of glycolipids though their acid hydrolysate products [C8, C10, C12, C12:1] in fermented okara extracts (FOE). LC-MS Q-ToF analysis has not found clear evidence of phenazine- 1-carboxamide (PCN) and rhamnolipids congeners in the samples. However, chemical assays have provided evidence for the presence of a pH-responsive foaming agent as an unintended response to pH changes when rhamnolipid standards and potentially rhamnolipids-containing samples were pH-adjusted during the methylene blue complexation assay. The challenge of using chemical assay to locate phenazine derivatives and rhamnolipid fractions was the substantial interference from the nutritiously rich okara substrate since both methods of measuring rhamnolipid content: anthrone reducing sugar assay, and methylene blue complexation assay have respectively shown a higher amount of reducing sugar and anionic surfactant ‘rhamnolipids’ in nonfermented extract as compared to fermented extract. This confuses the authenticity of ‘rhamnolipid’ detected in the fermented samples since the result might have been contributed by the remnants of the non-transformed okara substrate. The confirmed presence of PCA also does not dismiss the possibility of other compounds acting as algicides since P. chlororaphis could produce more than just phenazines or rhamnolipids. Microbial degradation of okara may also contribute algicidal component of a substrate origin, instead of bacterium origin since okara contains a rich unfractionated trove of amino acids and peptides which may function as algicides in their own rights. Faced with ambiguous results, further refinement to experimental designs and the existing hypothesis would serve as an impetus towards furthering the knowledge of how extracellular metabolites of P. chlororaphis may serve a more functional role within the food security and safety ecosystem and find its own niche as a green algicide within the current circular economy paradigm.